Notary Role in Making The Farmland Rental Agreement and Sharing Agricultural Land Effort in The District of Mojolaban Sukoharjo - Yuniarto Prasetyo Aji; Lathifah Hanim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Indonesian agricultural is in changing times in this era, the potential is still carrying out the manufacture of leases of agricultural land and businesses for agricultural crops is still supported by extensive farmland and irrigation as well as the notary's role in the making of a legal entity farmer groups. The purpose of research is to know and analyze the role of the notary in the manufacture of leases of agricultural land and land revenue sharing farming business. Identify and analyze the impact of what happens if there is a dispute in the lease agreement of agricultural land and businesses for agricultural land in the district of Mojolaban Sukoharjo. The result in this research has been done on the role of the notary in the manufacture of leases farmland and effort for the results of agricultural land, agricultural land lease do-written by hand while sharing agreements of farmland and new notaries role in the making a legal entity that is useful to the farmer groups laden capital receipts of the central government.Keywords: Role of the Notary; Rental Agreement; Profit and Sharing Agreement.